The dispute between Malaysia and Indonesia over the ND6 and ND7 sea blocks: a Malaysian perspective - Torla, Areej; Yusof, Salma; Mohd Kamal, Mohd Hisham (Springer, 2021)
Malaysia has asserted sovereign rights over the ND6 and ND7 sea blocks, which partially overlap with the Ambalat and East Ambalat sea blocks. Indonesia has also asserted sovereign rights over there. This article argues the validity of Malaysia’s claim over the ND6 and ND7 sea blocks by virtue of the Pulau Ligitan dan Pulau Sipadan case in which the International Court of Justice found that the 4°10′ N parallel mentioned in the 1891 Convention between Great Britain and the Netherlands Defining Boundaries in Borneo terminated on the east coast of Sebatik and did not extend seawards. This article finds that Malaysia may use the Sipadan and Ligitan Islands as a basis to assert sovereign rights over the ND6 and ND7 sea blocks. The authors also highlights several other documents including a 1954 British declaration and bilateral treaties between Malaysia and Indonesia.